Microstructure and tensile properties of friction stir processed Al-Si alloy - Abdulmalik, Samir Sani; Ahmad, Rosli; Usman, O Y (Scholars Middle East Publishers, 2018)
In this study, a solid state processing tool for microstructure modification and material properties enhancement; friction stir processing (FSP) was applied on the surface of as-cast Al-Si-Cu-Ni aluminium alloy. Samples were subjected to FSP using fixed tool rotation speed 1400 rpm and traverse speed 42 mm/min, with tool angle tilted 3˚.The influence of the FSP on the microstructure and tensile properties of the cast AlSi-Cu-Ni alloy samples were studied. Microstructural evolution of the samples was investigated using optical microscope (OM) and scanning electron microscope (SEM), tensile test carried out at 1 mm/min cross-head speed. The results showed that FSP improved the tensile strength of the samples by decreasing particles size and porosity. FSP improved the alloy strength by about 54%.